New 7D and Memristor-Based 8D Chaotic Systems: Computer Modeling and Circuit Implementation - Kopp, M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2024)
The most pressing modern problem of using chaotic systems in practice is the development of multi-channel information encryption methods. To solve these problems, there is a need to develop multidimensional chaos generators. In this paper, novel multidimensional 7D and 8D hyperchaotic systems are presented. It details a technique for creating a 7D dynamic system derived from a pre-existing 6D dynamic system. Additionally, this paper outlines the development of an 8D nonlinear dynamic system utilizing a memristor. An examination of innovative 7D and 8D dynamic systems was conducted, focusing on the determination of Lyapunov exponents, the construction of bifurcation diagrams, and the identification of equilibrium points along with their corresponding stability conditions for each system. As a result of computer modeling of 7D and 8D hyperchaotic systems in MATLAB-Simulink and Labview, phase portraits of numerous strange attractors were obtained. Finally, using Multisim software, electronic circuits for new 7D and 8D chaos generators were built, which demonstrated similar behavior as in the MATLAB-Simulink and LabView models.